Respon Imun Seluler Ayam Petelur Pascavaksinasi Avian Influenza Subtipe H5N1 Isolat dari Bali - Gusti Ayu Yuniati Kencana; Tri Komala Sari; I Nyoman Suartha; I Ketut Tomy Caesar Ramanda; Anak Agung Sagung Kendran (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2021)
Avian Influenza subtype H5N1 (AI-H5N1) is a malignant virus that is very detrimental to laying chickens because it is highly contagious and mutates easily. Prevention of AI-H5N1 disease in laying chickens is carried out by vaccination, therefore to maintain the quality of the vaccine, continuous research is needed. This study aims to determine the potential of AI-H5N1 vaccine isolates from Bali as measured based on cellular immune response based on total and differential leukocyte cells. Formation of antibodies is influenced by the nonspecific and specific immune system involving leukocytes, especially lymphocytes. Total of 40 layers of Novogen Brown strain were used for the research sample, kept since the age of one day on a commercial farm in Perean Village, Tabanan Regency, Bali. Laying chickens are vaccinated at 5 weeks of age by intramuscular injection. Total of 20 chikens were taken randomly and used for the sample. Blood draws were performed once pre-vaccination and five times each week after vaccination with anticoagulants. Total leukocytes were examined by an auto hematology analyzer, while differential leucocytes with thin blood smear stained with Giemsa. Total and differential leukocyte data were analyzed by means of the variance test followed by the Duncan test. Results showed that AI-H5N1 vaccination from Bali isolates could increase total and differential leucocytes of laying chickens and had significant effect on the mean total leukocytes, the absolute values of heterophyll cells, eosinophils, lymphocytes, and monocytes, but had no significant effect on post-vaccination basophil cells.